Formulation of safety predictors in construction sites through the lens of theory of planned behaviour: A dematel based model - Kang, Chun Xiang; Lee, Chia Kuang; Bujna, Marián; Chai, Changsaar (Penerbit Universiti Malaysia Pahang, 2024)
The construction sector drives our country’s economic growth and fosters the development of human resources. Yet, the industry faces a significant challenge with a heightened rate of workplace fatalities, making safety a pressing concern. Unsafe working environments and employee conduct contribute to the escalation of construction accidents. Addressing safety compliance and safety participation is critical for improving safety performance. Past studies have concentrated around technological approaches, leaving a notable gap in exploring behavioural interventions within the workplace. The critical factors that influence safety compliance intention and safety participation would be best explained by using Theory of Planned Behaviour (TPB). TPB posits that actual behaviour can be predicted by intention, while the formation of intention is mainly determined by attitude, subjective norms and perceived behavioural control. Although the TPB framework is considered, there remains a lack of evidence substantiating the correlation between the safety predictors, safety compliance intention, and safety participation. This study investigates the impact of safety predictors on both safety compliance intention and safety participation through the application of the Decision-Making Trial and Evaluation Laboratory (DEMATEL) technique. Through DEMATEL technique, 25 experts were enlisted to offer pairwise rankings regarding the predictors influencing both safety compliance intention and safety participation. The predictors examined in the study include Attitude, Subjective Norm and Perceived Behavioural Control. The research findings highlighted substantial interconnections among all safety predictors, with “Attitude” identified as the most influential predictor among them. Organizations should prioritize this to enhance safety performance. Enhancing safety performance in construction projects becomes feasible through comprehensive understanding and intervention in the interconnections among safety predictors, safety compliance intention, and safety participation.